2016
DOI: 10.1007/s10086-016-1558-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on colour changes of black alder and beech veneers

Abstract: In the present study, colour changes in black alder (Alnus glutinosa L. Gaertn.) and beech (Fagus sylvatica L.) wood veneers subjected to heat treatment at 190°C for different time spans were investigated. The potential of CIELab system and near infrared (NIR) spectroscopy were used to evaluate the colour changes. The changes in colour appeared mostly by the reduction in lightness which is related to the degradation of hemicelluloses during heat treatment in both wood species. It was found that black alder dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…The absolute values of corresponding ΔL* and ΔE* were similar in each batch, indicating that the greatest part of the colour variation was caused by lightness loss. Similar results were reported by Gonzáles-Peña and Hale (2009), Salca et al (2016), and Bekhta and Niemz (2003). The relationship between ΔL* and ML is plotted in Fig.…”
Section: Coloursupporting
confidence: 88%
“…The absolute values of corresponding ΔL* and ΔE* were similar in each batch, indicating that the greatest part of the colour variation was caused by lightness loss. Similar results were reported by Gonzáles-Peña and Hale (2009), Salca et al (2016), and Bekhta and Niemz (2003). The relationship between ΔL* and ML is plotted in Fig.…”
Section: Coloursupporting
confidence: 88%
“…Salca et al (2016) studied the effects of heat treatment on black alder and beech at 190 °C for different durations and revealed similar results. Additionally, they reported that the changes in color appeared mostly due to a reduction in lightness, which was related to the degradation of hemicelluloses during heat treatment.…”
Section: Color Changesmentioning
confidence: 73%
“…The yellowing of bleached chemical pulp proceeded during heat treatment by decay of mainly hemicellulose, which is thermally less stable than cellulose [24]. Thermal decomposition of hemicellulose and cellulose occur with high intensity at 180 and 340 • C, respectively [25]. reddened after heat treatment, probably because of formation of condensation products and degradation and/or oxidation products, such as quinone-like substances [10].…”
Section: Preparation and Color Evaluation Of Light-colored Ligninmentioning
confidence: 99%